Auditoría tributaria “comercial Don Pepe”, cantón Guayaquil, provincia del Guayas, período 2012 - Preciado Quirumbay, Gustavo Favian (2013)
The tax audit is a tool of modern evaluation, which takes greater hierarchy to laws and regulations imposed are rigorous. In this area the tax audit applied to commercial DON PEPE of the city of Guayaquil explains as the culture and knowledge of tax law of our country is important for tax and respond to the provision of the tax administration of our country. The research presents the theme according to the audit process properly structured through procedures and techniques as well as the verification of tax legislation that allowed issued a report determining the reasonableness of the controls applied to the management of taxes, drawing conclusions and present recommendations targeted to the fulfillment of tax obligations that the commercial DON PEPE is subject. In the implementation phase, it was verified that the information submitted to the tax administration, appropriate operations recorded in the accounting books and the supporting documentation; as well as to all economic transactions, in order to detect temporary and permanent differences and establish tax objections, in accordance with the accounting and tax regulations in the hardware company. Compliance with tax obligations in fiscal 2012 of commercial DON PEPE openly exposes employment compliance and substantive tests to check the transparency of tax operations; it was verified the existence of the tax obligations and their timely registration and tax filing; We examined the application of the rules of a tax nature, was made to the analysis of the Bills that directly affect the tax statement, financial statements, declaration forms to end with an audit opinion.